Analisis Deskriptif Kinerja Keuangan PT Medco Energi Internasional Tbk dan PT Energi Mega Persada Tbk Periode 2015–2024 - Faniah, Nur; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial performance of PT Medco Energi Internasional Tbk and PT Energi Mega Persada Tbk during the period 2015–2024 using a descriptive quantitative method, where the data used are secondary data in the form of annual financial statements obtained from Indonesia Stock Exchange as well as the official company websites, the analysis is conducted using financial ratios including liquidity ratio measured by Current Ratio (CR), profitability ratio measured by Return on Assets (ROA), and solvency ratio measured by Debt to Equity Ratio (DER), the results show that the financial performance of both companies experienced significant fluctuations throughout the observation period influenced by global oil and gas price dynamics, macroeconomic conditions, and energy sector policies, where in certain periods the companies faced declining performance due to falling commodity prices and increasing operational costs, however in subsequent periods there was a recovery trend particularly in PT Medco Energi Internasional Tbk which demonstrated more stable growth in profitability and assets compared to PT Energi Mega Persada Tbk, meanwhile in terms of solvency both companies still show relatively high leverage levels indicating the need for better capital structure management, overall, financial ratio analysis provides a clear overview of the companies’ financial conditions and can serve as a basis for decision-making for management, investors, and other stakeholders in evaluating the financial health of energy sector companies.